1990
DOI: 10.2307/2008691
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Interpolation and Conditionally Positive Definite Functions. II

Abstract: Abstract.We continue an earlier study of certain spaces that provide a variational framework for multivariate interpolation. Using the Fourier transform to analyze these spaces, we obtain error estimates of arbitrarily high order for a class of interpolation methods that includes multiquadrics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
195
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(195 citation statements)
references
References 2 publications
0
195
0
Order By: Relevance
“…Firstly, we want to establish the link between our function φ which occurs in the definition of the representer and the idea of a conditionally positive definite function. Secondly, we want to give an error estimate which is an improvement of one given in [12]. To investigate the idea of conditional positive definiteness, we utilise a definition from Gelfand and Vilenkin [5].…”
Section: Applications and Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, we want to establish the link between our function φ which occurs in the definition of the representer and the idea of a conditionally positive definite function. Secondly, we want to give an error estimate which is an improvement of one given in [12]. To investigate the idea of conditional positive definiteness, we utilise a definition from Gelfand and Vilenkin [5].…”
Section: Applications and Remarksmentioning
confidence: 99%
“…However, there is earlier unpublished work by Madych and Nelson which adopts very powerfully a dual viewpoint of conditionally positive definite functions linked to a variational theory. This work has been extended and enhanced by Madych and Nelson [11,12], Wu and Schaback [19] and in a series of papers by Schaback, which the reader can access through the survey [15]. The idea in all these papers is to use the theory surrounding conditionally positive definite functions to develop the correct setting for a variational approach to the above interpolation problem.…”
Section: Introductionmentioning
confidence: 99%
“…Based on earlier studies of [3], [4], [14], [15], [16], [34] among other things characterisations of the native function spaces have been surveyed in [11]. Interestingly enough, [11] proves that we do not obtain more information if we extend the definition of F ψ (Ω) to F ψ (R d ), since it can be shown that restriction of all functions from the latter to the domain Ω yields a function space that coincides with F ψ (Ω):…”
Section: Characterisations Of Native Spacesmentioning
confidence: 99%
“…-The paper [15] of Madych and Nelson provides a further example for the Gaussians ψ(x ) = e −α|x| although restricted to the univariate case d = 1 by…”
Section: Examplesmentioning
confidence: 99%
“…The function is conditionally positive definite of order 1 [10,21,28] on R 3 . Moreover, is in C 2 (R 3 ) [28, Theorem 4.1], so we can form its Hessian,…”
Section: Introductionmentioning
confidence: 99%